Public Discourse and Digital Customer Experience in Online Motorcycle Taxi Services: A Multimethod Analysis - Ferel Rizqia Maulana; Asep Miftahuddin; Eka Surachman; Yoga Perdana; Budhi Pamungkas Gautama; Arciana Damayanti (CV. Media Digital Publikasi Indonesia, 2026)
The digital technology has transformed the platform-based transportation services and now, digital customer experience is playing a pivotal role in the success of the service. But, there is a constant mismatch between what is expected from the services and what the users experience, which can be seen in the social media discourse. The goal of this study is to analyze the construction of digital customer experience, its communication and its impact on online motorcycle taxi services. The research uses a multi-method design, combining sentiment analysis, social network analysis, text network analysis, emotion classification, and trend analysis on social media discourse to get a comprehensive grasp of user-generated discourse and its complexity. The results show that the digital customer experience is multi-dimensional by nature, sometimes being characterized in a positive way and sometimes in a negative way, and the act of speaking publicly of it is a mixture of positive and negative. Furthermore, the discourse is structured, with the main actors being in the center of opinion formation and dissemination in the digital network. These findings enable the theoretical sophistication of the digital customer experience and the digital public sphere, since they show how individual experiences turn into collective perceptions, as a result of their interaction. For the practice, the study highlights the significance of businesses proactively engaging in digital conversations, enhancing their services, and effectively managing digital communities.